2010
DOI: 10.1071/bt10053
|View full text |Cite
|
Sign up to set email alerts
|

Biological indicators of climate change: evidence from long-term flowering records of plants along the Victorian coast, Australia

Abstract: We investigate the utility of using historical data sources to track changes in flowering time of coastal species in south-eastern Australia in response to recent climate warming. Studies of this nature in the southern hemisphere are rare, mainly because of a paucity of long-term data sources. Despite this, we found there is considerable potential to utilise existing data sourced from herbaria collections and field naturalists’ notes and diaries to identify native plant species suitable as biological indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Although phenological analyses of herbarium data offer unique insights into past responses, they model past responses only, and long-term phenological observation is necessary to fully understand present responses and model those in the future. To complement the herbarium data and test our models, we are directly monitoring Rhododendron phenology on Yulong Mountain, conducting artificial warming experiments, and documenting indigenous peoples' observations of change.This study joins other work from the past decade showing the value of herbarium collections to infer long-term phenology (10,11,43,48,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48, 52), and, in this study, the contrasting response of warming across different seasons.…”
supporting
confidence: 83%
“…Although phenological analyses of herbarium data offer unique insights into past responses, they model past responses only, and long-term phenological observation is necessary to fully understand present responses and model those in the future. To complement the herbarium data and test our models, we are directly monitoring Rhododendron phenology on Yulong Mountain, conducting artificial warming experiments, and documenting indigenous peoples' observations of change.This study joins other work from the past decade showing the value of herbarium collections to infer long-term phenology (10,11,43,48,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48, 52), and, in this study, the contrasting response of warming across different seasons.…”
supporting
confidence: 83%
“…The relevance of herbarium collections to a range of ecological conservation and biological studies has been, to date, largely underappreciated in Australia (Rumpff et al 2008). Indeed the application of herbarium vouchered specimens to comparative phenological studies is a relatively recent approach (Borchert 1996;Primack et al 2004;Bolmgren and Lonnberg 2005;Lavoie and Lachance 2006;Primack and Miller-Rushing 2009;Gallagher et al 2009;MacGillivray et al 2010).…”
Section: Mixture Models For Time Series: Disease-climate and Phenologmentioning
confidence: 99%
“…The timing of flowering and fruiting (phenology) is often influenced by temperatures in the month or two preceding flowering or fruiting (Fitter, Fitter, Harris, & Williamson, 1995;Panchen & Gorelick, 2015;Panchen, Primack, Aniśko, & Lyons, 2012). Phenological temperature sensitivity has been used to identify plants that are indicators of climate change and the responsiveness of plants to climate change (Bertin, 2015;Gallagher, Leishman, & Hughes, 2009;Menzel et al, 2006;Panchen et al, 2012;Rumpff, Coates, & Morgan, 2010;Springate & Kover, 2014). Herbarium specimens, pressed plants often collected in flower or fruit, provide a reliable historical record of flowering and fruiting phenology for use in phenology-climate change studies (Davis, Willis, Connolly, Kelly, & Ellison, 2015).…”
Section: Introductionmentioning
confidence: 99%